Comparison of the Morphology of Local Indonesian Fish (Tor soro) from Cultivation and Rivers Habitats on the Island of Java - Permadi, Jefri; Retnaningdyah, Catur; Marhendra, Agung Pramana Warih; Arfiati, Diana; Kurniawan, Nia (Journal of Posthumanism, 2025)
Mahseer fish is a local Indonesian fish whose population is decreasing in nature. Cultivation and restocking are conservation efforts aimed at maintaining the sustainability of natural populations. However, low genetic variation is often found in cultivated fish populations, making this an obstacle when released into the wild. Morphometric measurements are an efficient way to determine the population status of cultivated and wild Mahseer fish, which also provides initial information that has never been revealed before for the Mahseer fish species Tor soro on the island of Java. T. soro fish samples collected from the KF Balong fish pond in Subang, West Java, and the Progo tributary in Central Java. Nineteen morphological traits were used as morphometric data and analyzed using Principal Component Analysis (PCA). The results showed significant differences between cultivated ponds and wild populations, with PCA separating populations based on morphological traits, such as standard length (SL), body depth (BD), pre-anal length (PAL), body width (BW), pre-anal length (BW). -Dorsal (PDL), pre-ventral length (PVL). These findings indicate that the Mahseer fish species T. soro is able to maintain most of its non-functional characteristics in cultivation habitats, while functional characteristics such as BD adapt to environmental conditions. In addition, body deformities of Mahseer fish are also found in cultivated populations but not in wild populations.